TRIKATU CHURNA IN THE MANAGEMENT OF HYPOTHYROIDISM - Nabanita, *Das; Kuldeep, Choudhary; Kanika, Goswami (International Journal of Ayurveda and Pharma Research, 2018)
Thyroid disease especially Hypothyroidism is one of the commonest endocrine disorders worldwide and its prevalence of is increasing day by day. In allopathic system hypothyroidism is managed by replacement therapy with L-thyroxin which appears effective in restoring biochemical euthyroidism. However, studies continue to show problems in the management of this condition. Many patients report not feeling well with persistent symptoms despite adequate T4 replacement therapy. It has become necessary to find alternative medicine for managing hypothyroid symptoms. The main underlying pathology in Hypothyroidism is Hypometabolism in the tissues. This hypometabolism can be correlated to Mandagni in Ayurveda. Keeping this in mind we can plan the treatment of hypothyroidism in the line of treatment of Mandagni. In the treatment of Mandagni, on effective Ayurvedic formulation is Trikatu Churna. In this clinical study we have used Trikatu churna, as a dietary supplement in 30 patients from the OPD of Govt. Ayurvedic College and Hospital, Guwahati, to study its potential in the management of hypothyroidism. The statistical analysis of the data in trial group with Trikatu churna showed the value at 1.86 with level of significance at 1% (p<0.10). The Result of the clinical trial signifies that Trikatu churna is effective in the management of hypothyroidism.